Evaluation of Agronomic, Entomological and Breeding Aspects of Novel Sugarcane Clone under Climate Change Scenario: Novel Sugarcane Clone in Pakistan (Biological Sciences - PJSIR, 2022)
The increasing greenhouse gas emission and global warming during climate change result in sudden and extreme weather occasions. Climate change is affecting sugarcane production in the world, especially in the developing countries because of poor forecasting systems and mitigating strategies, sudden occurrence of pests and diseases. Varieties play an important role for sustainable sugarcane production. Varieties either lose their potential after few years release in field or become susceptible to pests and diseases under day by day changing climatic scenario. To combat climate changes and replace of exiting sugarcane varieties, different field experiments were planned at Sugarcane Research Institute, Faisalabad, Sugarcane Research Station, Khanpur and zonal testing of Sugarcane clone in adaptability trials at Progressive Sugarcane growers from 2002 to 2019 . All experiments were designed in randomized complete block design in three replications. Sugarcane clone S2003-US-127 were used in all experiments along with standards varieties HSF-240, CPF-249, SPF-234 and CPF-246. It is concluded from the study that sugarcane clone S2003-US-127 fetched higher cane yield (111.3 t/ha), sugar yield (14.1 t/ha), sugar recovery (12.72%) and higher economic Index than HSF-240, CPF-249, SPF-234 and CPF-246HSF. It is fast growing and matures earlier in 240-270 days. It has CPF 250 is resistant to red rot and smut.